Non-ammoniagenic proliferation and differentiation media for cultivated adipose tissue - Hubalek, S.; Melke, J.; Pawlica, P.; Post, M. J.; Moutsatsou, P. (Frontiers in Bioengineering and Biotechnology, 2023)
Ammonia (Amm), and its aqueous solved state, ammonium, which is produced from glutamine (Gln) metabolism, is a known inhibitor of stem cell proliferation in vitro. In the context of cultivated beef, primary bovine fibro-adipogenic progenitor cells (FAPs) need to be grown and differentiated for several weeks in vitro for the production of cultivated fat. In this study, the ammonium sensitivity of these cells was investigated by introducing ammonium chloride, which was found to inhibit their proliferation when above 5 mM and their adipogenic differentiation when above 2 mM. Novel serum-free proliferation and differentiation media were hence developed with the aim to suppress Amm production during expansion and adipogenesis. Glutamine substitutes, such as a-ketoglutarate (aKG), glutamate (Glt) and pyruvate (Pyr) were investigated. It was found that aKG based proliferation medium (PM) was the most effective in promoting and maintaining FAPs growth over several passages while the specific Amm production rate was reduced more than 5-fold. In terms of differentiation capacity, the substitution of glucose (Gluc) and Gln with galactose (Gal) and Pyr was shown to be the most effective in promoting FAPs differentiation into mature adipocytes, resulting in over 2-fold increase of fat volume per cell, while suppressing Amm production. Our findings suggest that FAPs do not require Gln as an essential nutrient but, on the contrary, possess all the necessary metabolic pathways to proliferate and subsequently differentiate in a Gln-free medium, resulting in decreased Amm production rates and seemingly synthesising glutamine de novo. These findings are important for prolonging the lifespan of culture medium, allowing for reduced costs and process interventions.